SPATIAL-RATING ASSESSMENT OF ENTREPRENEURIAL PERFORMANCE IN INDUSTRIAL PARKS OF RUSSIAN REGIONS - Piskun , Elena I.; Brusnikin , Konstantin N. (Economy of Regions, 2023)
Analysis of statistics at the micro-level shows that the development trends of a large number of resident entrepreneurial structures of industrial parks are characterised by adverse dynamics. Accordingly, assessment of the performance of entrepreneurial structures and improvement of their management models in the general system of industrial parks become more relevant. This paper presents a methodological approach to the construction of a spatial-rating assessment of the performance of entrepreneurial structures in the system of industrial parks functioning. As a result, two groups of Russian regions were identified, among which a potential resident, when making a decision on the placement of production facilities, can choose a region taking into account its investment attractiveness and industrial activity. Two discriminant groups of industrial parks were determined, the condition of which can be defined as economically inefficient and efficient, by evaluating parks with low and high values of the park rating level in terms of attractiveness for external investors and resident entrepreneurial structures. The proposed methodological approach can be applied to improve the quality of decisions on the formation of differentiated strategies for sustainable development of both individual entrepreneurial structures in the system of industrial parks and their clusters, and regions as a whole. It is recommended for both enterprises and industrial parks when making decisions on the formation of strategies and development scenarios, as well as for federal and regional authorities when designing documents for the territorial development on the strategic and tactical level.